1999
DOI: 10.1107/s090744499800626x
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength anomalous solvent contrast (MASC): derivation of envelope structure-factor amplitudes and comparison with model values

Abstract: A previous article [Fourme et al. (1995). J. Synchrotron Rad. 2, 36±48] presented the theoretical foundations of MASC, a new contrast-variation method using multiwavelength anomalous scattering, and reported the ®rst experimental results. New experiments have been conducted both at the ESRF (Grenoble, France) and at LURE-DCI (Orsay, France), using cryocooled crystals of three proteins of known structures and very different molecular weights. Amplitudes of fÀ T h g, thè normal' structure factors of the anomalou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 23 publications
(21 reference statements)
0
23
0
Order By: Relevance
“…MASC experiments have been performed on three protein structures of different molecular weight (Ramin et al, 1999). In all cases, ordered anomalous scatterers were found in addition to disordered atoms.…”
Section: The Solvent Phase In Proteins Mascmentioning
confidence: 99%
“…MASC experiments have been performed on three protein structures of different molecular weight (Ramin et al, 1999). In all cases, ordered anomalous scatterers were found in addition to disordered atoms.…”
Section: The Solvent Phase In Proteins Mascmentioning
confidence: 99%
“…It was found that the unfolding mainly involved the melting of a-helix into the disordered structures. The native lysozyme, which consists of 32% of a-helix, [71] unfolded irreversibly into a partially folded intermediate containing 6% of a-helix before it assembled into fibrils. The quantification of the secondary structure using far-UV CD and DUVRR spectra of protein were compared.…”
mentioning
confidence: 99%
“…The calculation of the Fourier transform (the molecular envelope) requires the derivation of phases associated with these amplitudes. This is a non-trivial problem, which we are currently addressing by several methods (Ramin, 1999;R. Kahn, unpublished), including the use of maximum entropy and likelihood ranking to test envelope hypotheses (Bricogne, 1993).…”
Section: From Mad To Mascmentioning
confidence: 99%
“…The comparison between experimental and model values has shown that amplitudes from envelope structure factors G(h) derived from MASC data are meaningful (Ramin et al, 1999). The future of this method is strongly dependent on the availability of an ef®cient procedure for phasing these coef®cients.…”
Section: From Mad To Mascmentioning
confidence: 99%